Stable Carbon Isotope Fractionation in Chlorinated Ethene Degradation by Bacteria Expressing Three Toluene Oxygenases - Clingenpeel, Scott; Moan, Jaina; Conley, Danielle M.; Hungate, Bruce A.; Watwood, Mary E. (Frontiers in Microbiology, 2012)
One difficulty in using bioremediation at a contaminated site is demonstrating that biodegradation is actually occurring in situ. The stable isotope composition of contaminants may help with this, since they can serve as an indicator of biological activity. To use this approach it is necessary to establish how a particular biodegradation pathway affects the isotopic composition of a contaminant. This study examined bacterial strains expressing three aerobic enzymes for their effect on the 13C/12C ratio when degrading both trichloroethene (TCE) and cis-1,2-dichloroethene (c-DCE): toluene 3-monoxygenase, toluene 4-monooxygenase, and toluene 2,3-dioxygenase. We found no significant differences in fractionation among the three enzymes for either compound. Aerobic degradation of c-DCE occurred with low fractionation producing δ13C enrichment factors of −0.9 ± 0.5 to −1.2 ± 0.5, in contrast to reported anaerobic degradation δ13C enrichment factors of −14.1 to −20.4‰. Aerobic degradation of TCE resulted in δ13C enrichment factors of −11.6 ± 4.1 to −14.7 ± 3.0‰ which overlap reported δ13C enrichment factors for anaerobic TCE degradation of −2.5 to −13.8‰. The data from this study suggest that stable isotopes could serve as a diagnostic for detecting aerobic biodegradation of TCE by toluene oxygenases at contaminated sites.